PENGENTASAN KEMISKINAN DI PERDESAAN: PENGEMBANGAN SDM, PENGUATAN USAHA, DAN INOVASI PERTANIAN (Forum Penelitian Agro Ekonomi, 2024)
Poverty is an all-time problem. The process of inheritance of poverty from generation to generation will continue if there is no breakthrough to alleviate poverty. This literature study aims to determine the role of human resource development, strengthening of farmers’ business and agricultural innovation in poverty alleviation. Although poverty in Indonesia has decreased significantly, the data showed that the number of poor people is still concentrated in rural areas. The development of human resources and the strengthening of farmers' business institutions, therefore, become medium-term and long-term strategic efforts for poverty alleviation in rural areas. Challenges to sustainable agricultural production in the future will require combined efforts of technological and innovation development, improvement of agricultural policies, and strengthening of agricultural institutions. Agricultural research and development should be focused on enhancing sustainable production.